Perceptions and Experiences of Academic Integrity and Group Work in Post-Graduate Management Courses: Strategies and Risks - Kader, Mo (Canadian Perspectives on Academic Integrity, 2021)
Student perceptions of group assignments indicate that there are lower levels of plagiarism or contract cheating in these assessments given the collective nature of the work, while individual assignments, particularly reports, are perceived as easier to cheat in. This paper examines the perceptions and the experiences of post-graduate management students and teaching staff in the level, type and source of plagiarism as it relates to group versus individual assignments. It compares the views of the academic literature on plagiarism with the student’s own perceptions and with the tendency to cheat in different forms of group and individual assessment. It further presents strategies for the mitigation of academic plagiarism and evaluates the risks arising from over-dependence on group assessments in an attempt to minimise plagiarism. Practical implications as well as theoretical concepts are addressed that may help develop effective strategies to address academic plagiarism.